The effect of adjunctive use of melatonin as a supplement on serum ferritin level in periodontal patients: A randomized, controlled trial - Masoumeh Faramarzi; Mehrnoosh Sadighi; Mohammadtaghi Chitsazi; Mahdieh Esmailzadeh; Ghazale Foladvand (Wolters Kluwer Medknow Publications, 2021)
Background: Ferritin is an acute-phase protein that is increased in inflammatory diseases. Melatonin has been studied due to its antioxidant effects and the elimination of free radicals. The aim of this study was to evaluate the effect of melatonin supplement as an adjunct to routine periodontal treatment on serum ferritin levels in patients with periodontitis. Materials and Methods: Forty patients with chronic periodontitis were included in this randomized controlled clinical trial study. Twenty patients received nonsurgical periodontal treatment and twenty patients received nonsurgical periodontal treatment with adjunctive use of melatonin. Serum ferritin concentrations and periodontal parameters were recorded at baseline and 3 months after periodontal therapy. Serum ferritin level and periodontal parameters comparison at baseline and 3 months after periodontal treatment was done by Wilcoxon signed-rank test and paired sample t-test, respectively. Differences between test and control groups were evaluated by Mann-Whitney U-test for ferritin level and independent t-test for periodontal parameters, and a P ≤ 0.05 was considered statistically significant. Results: Serum ferritin level decreased in both the control and test group in 3 months follow-up compared to baseline (P < 0.001). The reduction in ferritin levels in the test group was more than the control group, but this difference was not statistically significant (P = 0.414). Improvement in periodontal parameters were not significant between two groups (P = 0.489), but improvement rates in the test group were more than control. Conclusion: Melatonin, as an adjunct to periodontal therapy, showed additional benefits in the reduction of serum ferritin levels and improvement of periodontal parameters.